An Empirical Analysis of Allocative Efficiency of Nigerian Commercial Banks: A DEA Approach - Akeem, Usman Owolabi; Moses, Fadipe (International Journal of Economics and Financial Issues, 2014)
This paper investigated an empirical analysis of allocative efficiency of Nigerian commercial Banks between the years 2002 to 2011. Ten Nigerian Banks were randomly selected out of 15 banks operating in Nigeria. For this intention, the Data Envelopment Analysis (DEA) model was used with three input variables (deposits, operating expenses, and assets) and four output variables (loan and advances, investment, Interest income, and non-interest income). The mean allocative efficiency, for the period examined stood at 0.896 (89.6%). This mean result depicted the fact that Nigerian banking sector generally needs managerial attention beyond the emphasis on continual banking reforms of recapitalization, merger and acquisition and the likes so as to be ranked with the global perspective. Keywords: Data Envelopment Analysis; Allocative efficiency; Decision-Making Units; Financial Intermediation; JEL Classifications: C22; G22; L12